Effectiveness of Nutritional Intervention on Bone Mineral Density among Women Aged 30-50 Years in South India - Silpa Chintham (Medsci Publications, 2024)
Introduction: By 2050, low bone mineral density in women is expected to increase by 40% globally, considerably increasing the burden of osteoporosis in future generations, which necessitates greater focus on preventive measures. Hence, it was planned to study the effectiveness of calcium rich nutritional intervention on bone mineral density among women aged 30-50 years in South India. Methods: A quasi-experimental pre-test and post-test control group design was conducted among randomly selected 20 urban and rural women aged 30-50 years. Calcium rich nutritional mix was given for 16 weeks to the interventional arm and for control arm, education on importance of calcium rich diet was given. Bone mineral density was measured by DEXA scan pre and post intervention. Descriptive and inferential statistics were used to analyse the data. Results: Before intervention, all the women (100%) had mildly reduced bone mineral density; post intervention, majority of the women (80%) had normal bone mineral density, only 20% had mildly reduced bone mineral density. In the control group, 100% had mildly reduced bone mineral density before receiving health education and after 16 weeks of education, 90% had mildly reduced bone mineral density and only 10% had normal bone mineral density. Conclusion: Calcium rich nutritional intervention given to the experimental group women resulted in a significant improvement in their bone mineral density. However, risk can be lowered by leading a healthy lifestyle that includes enough quantities of dietary calcium, vitamin D, and protein, frequent weight-bearing activity.